A Light from Finland: Uncovering Teachers’ Role in Evaluating Students’ Learning through Parent-Teacher Conferences - Tholchah, Muchammad (Universitas Islam Negeri Walisongo Semarang in collaboration with PD PGMI Indonesia, 2025)
The implementation of the Merdeka curriculum has posed significant challenges for teachers, particularly in learning assessment practices. This study explores the roles of Finnish teachers in evaluating student progress during parent-teacher conferences (PTCs) using a qualitative, autoethnographic approach guided by teacher practice theory. The findings highlight that Finnish teachers utilize comprehensive materials and diverse sources, playing as mentors for children by empowering students to articulate their learning experiences and collaborate with parents through fostering shared educational responsibilities with parents, which indicates the practice represented beyond solely the pedagogical domain. However, the study cautions against directly replicating the Finnish model in Indonesia due to the limited number of participants and differences in educational systems, cultural contexts, and institutional frameworks. Future research should include a larger participant pool to provide a broader understanding of PTCs in Finland, enabling Indonesia to adapt these practices effectively and resolving the problem of student learning assessment in the Merdeka curriculum.